ІМПУЛЬСНЕ МОДЕЛЮВАННЯ УРБАНІЗОВАНИХ ТЕРИТОРІЙ ЯК ФАКТОР ПЕРЕХОДУ ДО ЕТАПУ ПОСТ-ІНДУСТРІАЛЬНОГО МІСТОБУДУВАННЯ (World Science, 2018)
The article studies the problem of a gradual change in the direction of urban discourse under the influence of critical re-considering of the heritage in modernists projecting and the range of social and technological initiatives implemented on the verge of 21st century. One of the features that characterizes the modern approach to urban development is a diversity of the material, dedicated to the evolution of urbanism in the 21st century (which deals with various forms of its perspective and retrospective). Such scope of data rises a lot of questions about the development of a certain system of its analysis regarding the balance of dominating topics and tasks. The given article studies main directions of scientific approach to the current state and perspective ways of urban evolution, based mainly on the potential incorporated in the traditional industrial urban development to reflect the phenomena and changes of a post-industrial city.